Comparison of black carbon measurement techniques for marine engine emissions using three marine fuel types. Issue 1 (25th November 2021) - Momenimovahed, Ali; Gagné, Stéphanie; Martens, Patrick; Jakobi, Gert; Czech, Hendryk; Wichmann, Volker; Buchholz, Bert; Zimmermann, Ralf; Behrends, Brigitte; Thomson, Kevin A.
Abstract: Black carbon (BC) mass concentration from internal combustion engines can be quantified using a variety of different BC measurement techniques. We compare the relative response of several commercial instruments with different measurement principles to different types of marine exhaust emissions. Exhaust samples were generated using a high-speed 4-stroke marine diesel engine at various engine operating conditions from low to high engine loads. Three different fuel types—diesel, distillate marine oil grade A (DMA) and intermediate fuel oil (IFO)—were used to generate soot particles with a wide range of physical, chemical and optical properties. Based on the standard deviation of the results at all engine conditions evaluated in the present study, the overall spread between the instruments was 24% for diesel, 30% for DMA and 37% for IFO samples. For samples with extremely high organic content (at 10% engine power), the agreement was poor and the standard deviation of the mass concentrations estimated from different instruments was 50% for diesel with OC/EC ≈ 45 and 72% for DMA with OC/EC ≈280. For IFO particles, more scattered mass concentrations were reported by different instruments at all engine loads, possibly due to very complex chemical composition and different optical properties in comparison with well-characterized soot particles. We explain the differences in reported values by combining information on exhaust composition with the measurement principles used in each instrument.